cubic curve sketching
Download
Skip this Video
Download Presentation
Cubic Curve Sketching

Loading in 2 Seconds...

play fullscreen
1 / 7

Cubic Curve Sketching - PowerPoint PPT Presentation


  • 141 Views
  • Uploaded on

Cubic Curve Sketching. Basic cubic shapes . Unlike quadratics cubic usually have two bumps e.g. But sometimes the have no bumps. y =x 3 -3x 2 +3. y =-x 3 +3x 2 +3. y =x 3. Example: Sketch y=(x-1)(x+2)(x+3). Here are the steps for sketching cubic curves

loader
I am the owner, or an agent authorized to act on behalf of the owner, of the copyrighted work described.
capcha
Download Presentation

PowerPoint Slideshow about ' Cubic Curve Sketching' - connor


An Image/Link below is provided (as is) to download presentation

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.


- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -
Presentation Transcript
slide2

Basic cubic shapes

Unlike quadratics cubic usually have two bumps e.g.

But sometimes the have no bumps

y=x3 -3x2 +3

y=-x3 +3x2 +3

y=x3

slide3

Example: Sketch y=(x-1)(x+2)(x+3)

Here are the steps for sketching cubic curves

Find x intercepts by solving y=0

Find y intercept by putting x=0

Find out what happens as x get very big and very small (Limits)

slide4

Find x intercepts by solving y=0

Solve:

(x-1)(x+2)(x+3)=0

Equate factors to zero

X-1=0

X+2=0

X+3=0

Intercepts are: x=1, x=-2, x=-3

slide6

3. Find out what happens as x get very big and very small (Limits)

If x3 has a positive coefficient (multiplier) then as x -> ∞ y -> ∞

If x3has a negative coefficient then as x -> ∞ y -> - ∞

In our example

y=(x-1)(x+2)(x+3)

The coefficient of x3 is 1 so as x -> ∞ x -> ∞

slide7

Here is the final sketch

y=(x-1)(x+2)(x+3)

ad